2020
DOI: 10.1007/s11199-019-01115-y
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Test of the Cosmetics Dehumanization Hypothesis: Heavy Makeup Diminishes Attributions of Humanness-Related Traits to Women

Abstract: Objectification theory suggests that sexualization has significant dehumanizing consequences for how perceivers see women. To date, research has mostly documented how sexualized bodies in the mass media are objectified and dehumanized. The purpose of the present work was to test the novel cosmetics dehumanization hypothesis (CDH), that is, that subtler manifestations of sexualization, such as heavy makeup, might influence the way people attribute humanness-related traits to women. Across four experiments, 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Moreover, physical appearance has been linked to dehumanization through facial width ( Deska et al. , 2018 ), obesity ( Kersbergen and Robinson, 2019 ) and even use of cosmetics ( Bernard et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, physical appearance has been linked to dehumanization through facial width ( Deska et al. , 2018 ), obesity ( Kersbergen and Robinson, 2019 ) and even use of cosmetics ( Bernard et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to objectification theory, Western women live in a society that emphasizes beauty and appearance (Bernard and Wollast 2019;Bernard et al 2020;Fredrickson and Roberts 1997). In line with this theory, a plethora of literature has revealed the treatment of women as sex objects in media (for a state of empirical research, see Ward 2016) and interpersonal interactions (Kozee et al 2007).…”
Section: How Self-compassion Moderates the Relation Between Body Survmentioning
confidence: 99%
“…Further, a relatively less explored dimension of person perception is the attribution of humanness to other individuals. Existing literature has demonstrated that women who engage with beautification are perceived to be less human [ 44 ]. As such, we are likely to see decreased perceptions of humanness among plastic surgery recipients.…”
Section: Introductionmentioning
confidence: 99%